ANALISIS IMPLEMENTASI PROGRAM KURIKULUM MERDEKA BELAJAR SEBAGAI STRATEGI PENINGKATAN MUTU PENDIDIKAN - Rahmawati Alwi; Rosi Indriyani (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
The purpose of this study was to describe and analyze (1) the implementation of students' learning rights, (2) the obstacles encountered in the implementation of students' learning rights. The type of research used is qualitative descriptive research, the research location is at SMK Negeri Leuwiliang. The results of the study show that (1) the implementation of students' learning rights has been carried out at the SMKN school since the beginning of the policy's implementation (2) there are several obstacles faced including: a) Some students are not ready for technology, students are still used to being told by teachers and not fully independent, b) Because they have no experience of the independent curriculum, limited references and training, c) Teachers have not fully collaborated, d) Not all stakeholders understand the substance of the Implementation of the Independent Learning Curriculum, e) Still in the process of adapting to the Independent Curriculum so that it is still not optimal. f) Digital access is often an obstacle, sometimes the network is unstable, making it difficult for students and teachers to access learning resource materials, g) Limitations of references and media are problems encountered that make it an obstacle to the learning process